2005
DOI: 10.1029/2005gl022641
|View full text |Cite
|
Sign up to set email alerts
|

Springtime cloud condensation nuclei concentrations on the west coast of Korea

Abstract: [1] Cloud condensation nuclei (CCN) measurements were made with the Desert Research Institute (DRI) instantaneous CCN spectrometer at the Korea Global Atmosphere Watch (GAW) Observatory (KGAWO) (36°32 0 N, 126°19 0 E) on the west coast of the Korean Peninsula from May 1 -22, 2004. A TSI CPC3010 counter simultaneously measured condensation nuclei (CN). For seven of these days, submicron aerosol size distributions were also measured with an SMPS. Data were classified maritime or continental according to air mass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
26
2

Year Published

2005
2005
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(34 citation statements)
references
References 15 publications
6
26
2
Order By: Relevance
“…The average N CCN /N CN of this study (0.32) was higher than that measured in Vienna (0.13 at SS 0.5 %, CN 13-929 nm) and Finland (0.1-0.3 at SS 0.2 %, CN 3-1000 nm). The increased N CCN /N CN was derived at larger SS in urban environments such as Shanghai (0.47 at SS 0.8 %, CN 10-10 000 nm) and Korea (0.64 at SS 1.0 %, CN 10-500 nm) (Yum et al, 2005;Burkart et al, 2011;Sihto et al, 2011;Leng et al, 2013).…”
Section: Physical and Chemical Properties Of Aerosolmentioning
confidence: 99%
See 2 more Smart Citations
“…The average N CCN /N CN of this study (0.32) was higher than that measured in Vienna (0.13 at SS 0.5 %, CN 13-929 nm) and Finland (0.1-0.3 at SS 0.2 %, CN 3-1000 nm). The increased N CCN /N CN was derived at larger SS in urban environments such as Shanghai (0.47 at SS 0.8 %, CN 10-10 000 nm) and Korea (0.64 at SS 1.0 %, CN 10-500 nm) (Yum et al, 2005;Burkart et al, 2011;Sihto et al, 2011;Leng et al, 2013).…”
Section: Physical and Chemical Properties Of Aerosolmentioning
confidence: 99%
“…More fractions of particles larger than 80 nm were activated into CCN during the hazy case (86 %) and foggy-hazy case (84 %) than that during the clear case (76 %). Although in different SS conditions, N CCN was measured at other urban or urban-like environments such as the west coast of Tasmania (32 cm −3 ) and the west coast of Korea (5292 cm −3 ) at SS 1.0 % (Yum et al, 2004(Yum et al, , 2005, and Mexico city (3000 cm −3 ), Ireland (208-346 cm −3 ) and Vienna (820 cm −3 ) at SS 0.5 % (Baumgardner et al, 2003;Reade et al, 2006;Burkart et al, 2011). An even larger N CCN (6000 cm −3 ) was measured at SS 0.17 % in Beijing (Deng et al, 2011).…”
Section: Physical and Chemical Properties Of Aerosolmentioning
confidence: 99%
See 1 more Smart Citation
“…To incorporate the effects of CCN in meteorological models at all scales, from large eddy simulation (LES) to global climate models (GCM), knowledge of the spatial and temporal distribution of CCN in the atmosphere is essential (Huang et al, 2007). Several studies reported CCN measurements from various regions around the world (e.g., Andreae, 2009;Andreae and Rosenfeld, 2008;Bougiatioti et al, 2009;Broekhuizen et al, 2006;Chang et al, 2010;Dusek et al, 2006Dusek et al, , 2010Ervens et al, 2010;Gunthe et al, 2009;Hudson and Yum, 2002;Lance et al, 2009;Roberts et al, 2001Roberts et al, , 2002Roberts et al, , 2006Shantz et al, 2010;Wang et al, 2008Wang et al, , 2010Yum and Hudson, 2004;Yum et al, 2005). However, the actual influence and relative importance of aerosol size distribution, chemical composition, and mixing state on the variability and predictability of CCN concentrations remained a subject of continued discussion (e.g., Broekhuizen et al, 2006;Dusek et al, 2006;Hudson, 2007;Cubison et al, 2008;Wang et al, 2008;Bougiatioti et al, 2009;Gunthe et al, 2009;Ervens et al, 2010;Jurányi et al, 2010;Rose et al, 2010a;Wex et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The CCN concentrations were found to be higher compared to other remote areas of the world such as Island of Tasmania in Australia and Mace Head in Ireland due to transported anthropogenic aerosol. Yum and Hudson (2005) performed CCN measurements with the CCN spectrometer at the Korea Global Atmosphere Watch (GAW) Observatory (KGAWO) on the west coast of Korean peninsula. Data was classified as maritime or continental according to the air mass back trajectories.…”
mentioning
confidence: 99%